Cultural adaptation and psychometric properties of the Persian version of the Affordance in the Home Environment for Motor Development - Kavousipor, Somaye; Rassafiani, Mahdi; Ebadi, Abbas; Solimani, Farin; Hosseini, Ali; Gabbard, Carl (Iranian Journal of Child Neurology, 2019)
Objective. The intent of this study was to translate the Affordance in the Home Environment for Motor Development (AHEMD) scales (3-18 months [IS] and 18-42 month [SR] versions) into Persian, and examine its cultural adaptation and psychometric properties. Method. A four stage process was conducted: translation of the questionnaires (use of International Quality of Life Assessment protocol), cultural adaptation, and determination of its psychometric properties. Qualitative judgments were provided by 11 experts and 30 mothers for interview sessions. Quantitative data were gathered using 212 mothers. Results. For the IS version, validity values ranged from 0.63 to 0.95. Intraclass correlation coefficient for reliability of total score was 0.87 (0.83-0.97), and was Cronbach’s alpha (0.75). Validity for the AHEMD-SR ranged from 0.63 to 0.90, with reliability for total score at 0.98 (0.98-0.99, ICC). Cronbach’s alpha for this version was 0.84. Correlations with SES were significant for both scales: IS (r = 0.40) and AHEMD-SR (r = 0.42). Conclusion. Both translated versions of the AHEMD were determined to be valid and reliable assessments of the home environment of Iranian young children. Keywords: Home environment, Assessment, Validity and reliability, Motor ability, Affordance